Operant measurement of auditory threshold in prelingually deaf users of cochlear implants: II - da Silva, Wagner R.; de Souza, Deisy G.; Bevilacqua, Maria Cecília; Lopes Jr., Jair [UNESP] (American Psychological Association (APA), 2011)
Two experiments evaluated an operant procedure for establishing stimulus control using auditory and electrical stimuli as a baseline for measuring the electrical current threshold of electrodes implanted in the cochlea. Twenty-one prelingually deaf children, users of cochlear implants, learned a Go/No Go auditory discrimination task (i.e., pressing a button in the presence of the stimulus but not in its absence). When the simple discrimination baseline became stable, the electrical current was manipulated in descending and ascending series according to an adapted staircase method. Thresholds were determined for three electrodes, one in each location in the cochlea (basal, medial, and apical). Stimulus control was maintained within a certain range of decreasing electrical current but was eventually disrupted. Increasing the current recovered stimulus control, thus allowing the determination of a range of electrical currents that could be defined as the threshold. The present study demonstrated the feasibility of the operant procedure combined with a psychophysical method for threshold assessment, thus contributing to the routine fitting and maintenance of cochlear implants within the limitations of a hospital setting.
Keywords: Cochlear implant; Deaf children; Go/No Go; Mouse click; Simple auditory discrimination; Threshold measurement; auditory discrimination; auditory stimulation; auditory threshold; child; clinical article; cochlea prosthesis; controlled clinical trial; controlled study; electrode; electrostimulation; feasibility study; female; human; infant; instrumental conditioning; learning; male; perception deafness; preschool child; psychophysics; sound intensity; stimulus response; task performance